Thermal aging of HTPB/IPDI-based polyurethane as a function of NCO/OH ratio - Luciene Dias Villar; Thiago Cicaglioni; Milton Faria Diniz; Marta Ferreira Koyama Takahashi; Luis Cláudio Rezende (Materials Research, 2011)
Thermal aging of hydroxy-terminated polybutadiene/isophorone diisocyanate (HTPB/IPDI)-based polyurethane was studied as a function of NCO/OH ratio (1.0 and 0.85). Samples were aged in air ovens at 50, 60, 65, and 70 ºC for periods of time from 1 to 34 weeks. Changes in chemical (swelling testing and FT-IR spectroscopy) and mechanical (tension testing and hardness) properties were evaluated throughout the aging assays. Correlation between equilibrium swelling ratio and elastic modulus, coupled with changes in FT-IR spectra, indicated oxidative cross-linking as the dominant mechanism for both molar ratios investigated. However, determination of Arrhenius activation energy resulted in values of (82 ± 10) kJ.mol-1 and (156 ± 30) kJ.mol-1 for 1.0 and 0.85 NCO/OH ratios, respectively, thus revealing faster oxidative degradation kinetics for higher urethane linkage networks.